Jesuits in North America in the Seventeenth Century. - Parkman, Francis (Andrews UK Ltd, 2012)
The second in Francis Parkman's fantastic series of histories of the European colonists, 'France and England in North America'. This volume looks at the 17th century French Jesuit missionaries in Canada, starting from their arrival in 1632.